Influence of outlet geometry on cooling and pressure drop in a 5G radio device_ An experimental and CFD study on the pressure drop and heat transfer associated with forced air flow through a 5G remote radio device at Ericsson AB - Shaikh, Mohammed Mubeen (My University, 2022)
With the rapid increase in the number of 5G users every year, the demand for in creased connectivity and reduced lag time is consequently rising. An accelerated growth in the number of 5G radio devices is expected and along with it, the energy requirements of said devices is also expected to sharply rise. It is vital that the cooling and ventilation in these radio devices is optimized to ensure maximum effi ciency. In this study, the effect of the outlet geometry of radio devices on the overall internal ventilation and the associated cooling is observed. Four outlet geometries (Hexagonal, Louvers, Tall stripes, Uni-gill) are studied both experimentally and by steady-state Computational Fluid Dynamics (CFD) simulations at Ericsson AB. The experimental tests were performed to simulate the heat generation within the radio device and a wind tunnel was used to mock the air flow within it. The hexag onal outlet shape proved to have required a lower pressure drop and hence lower fan power requirement as compared to the Louvers outlet shape. Better heat sink temperature distribution was also observed on the hexagonal outlet shape. Having conducted the CFD simulations, it was understood that the outlet geome tries that resulted in higher Reynolds numbers in the heat sink produced lower pressure drops and better cooling. A Nusselt number correlation was also used to validate the heat transfer in the Heat Sink ducts and the calculated values agree with the literature. The production of acoustical noise with the hole patterns was not explicitly studied but was observed during the experimental tests and holds a scope for future studies.
Keywords: 5G radio, CFD, heat sink tests, outlet geometry, Nusselt number, internal flow.